Fabrication of MoS2‐Decorated Nickel‐Cobalt Bimetal Phosphide Nanocubes as Efficient Electrocatalysts for Hydrogen Evolution. Issue 40 (25th October 2019) - Feng, Jianhui; Zhou, Hu; Chen, Danyang; Shao, Jinxiao; Diao, Guowang; Yuan, Aihua
Abstract: Nickel‐cobalt bimetal phosphides were prepared via the phosphidation treatment of NiCo‐based Prussian blue analogue (PBA). Subsequently, the core‐shell structures of NiCoP@MoS2 were successfully assembled through a solvothermal reaction, where the NiCoP substrates were uniformly and randomly covered by MoS2 nanosheets. The resulting hybrids exhibited significantly superior catalytic activities towards hydrogen evolution reaction (HER) in 0.5 M H2 SO4 to bare MoS2 . The optimal catalyst afforded the best HER performance with a low overpotential of 138 mV at 10 mA cm −2 and Tafel slope of 78.1 mV dec −1, together with high stability and durability. The excellent HER properties of hybrids mainly originated from the unique core‐shell architecture and the intrinsic natures of MoS2 and PBA‐derived bimetal phosphides. Abstract : The core‐shell structures of NiCoP@MoS2 have been demonstrated as highly effective electrocatalysts towards HER, which originates from the unique morphology and intrinsic nature of each component. This study provides a general methodology to design and construct these hybrids involving MoS2 and metal phosphides with controlled nanostructures for further electrochemical applications.